Characterization of dams containing rejects located in the state of Minas Gerais (Research, Society and Development, 2019)
The availability of mineral reserves located in the State of Minas Gerais makes this one of the most important in the Brazilian mining industry. However, for the commercialization of ores, in terms of content and grain size required by the market, a beneficiation process is required, which generates the by-product the tailings, usually destined for containment dams, which have a great potential for pollution. Thus, this research aimed at the classification of tailings dams located in the State of Minas Gerais. For this purpose, the documentary analysis of the data contained in the State dams inventory for the year 2017 was used. The 302 dams registered in the inventory were characterized in terms of class, height, volume, spatial distribution and stability condition. The results showed that most of the tailings dams present in the State are of high environmental damage potential but characterized by a low height (